Research of Magnetic Shielding Effect of Air-core Reactor - ZHANG Bo; GAO Shiping; WANG Yan; LIN Yong; DING Mingwei; WANG Dongqing (机车电传动)
For a shielding system with a magnetic board above an air-core reactor of urban rail vehicle, in order to analyze all kinds of facts that affect the magnetic shielding effects, 3D model of the magnetic board shielding system using the Ansoft Maxwell finite element software was established, and finite element simulation experiments were put forward. Effects of different material’s types, different thickness and different magnetic coil current were discussed, the results of which had important guidance for the research on air-core reactor magnetic shielding.